A Comprehensive and Critical Review on Ethnopharmacological Importance of Desert Truffles: Terfezia claveryi, Terfezia boudieri, and Tirmania nivea. (1st November 2022) - Veeraraghavan, Vishnu Priya; Hussain, Sardar; Papayya Balakrishna, Janardhana; Dhawale, Lavina; Kullappan, Malathi; Mallavarapu Ambrose, Jenifer; Krishna Mohan, Surapaneni
ABSTRACT: Mushrooms and truffles have gained a lot of attention due to their aroma for culinary use and high nutritional content. Truffles, which are distributed in many African and European countries, have been successfully grown in recent times. Truffles are mycorrhizal fungi, which represent a symbiotic association of fungi Terfezia with the roots of Helianthemum species as host. Apart from being used as edibles, various biological uses of truffles have been reported which include antioxidant antiviral, antimicrobial, hepatoprotective, anti-mutagenic, and anti-inflammatory activities. In this review, we have summarized their classification with special emphasis on chemical constituents and biological activities of three desert truffles, viz. Terfezia boudieri, Terfezia claveryi, and Tirmania nivea . Strong antioxidant potential has been shown by these truffles along with antibacterial and antiviral effect in vitro and in animal studies (preclinical studies). These truffles have also been assessed for their anti-cancer and antidiabetic properties and were used as a folk medicine for their aphrodisiac powers which has been proven by various in vivo studies. The main drawback with the use of these truffles is that their bioactive components and properties have not been well studied. The detailed studies on these aspects would help in the use of these truffles for medicinal purposes in clinics.